Republic of Croatia : Staff Report for the 2014 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2014)
This 2014 Article IV Consultation highlights that Croatia remains stuck in an unusually drawn out recession. In 2013, real GDP contracted for the 5th consecutive year, and stands now at less than 90 percent of the end-2008 level. Unemployment has risen to 17 percent. Domestic demand remains depressed as corporations and households focus on reducing excessive debts accumulated in the 2000s. Exports and foreign direct investment are also feeble. The outlook is for an additional contraction in 2014 of almost 1 percent. Real domestic demand would remain feeble, reflecting both weak private sector demand and fiscal consolidation.